By the River Piedra I sat down and wept - Coelho, Paulo; Clarke, Alan (Alan R.) ([San Francisco, CA] Harper SanFrancisco, 1996)
"The story of a young Spanish woman, Pilar, and her encounter with her lost love, an unnamed spiritual seeker who comes to worship the feminine face of God. Clarke's translation is, as usual, somewhat hurried and condensed as if he's impatient with Coelho's admittedly belabored and self-consciously poetical style"--Handbook of Latin American Studies, v. 58
Originally published: Rio de Janeiro : Editora Rocca, c1994
The text translate from Portugese to English
1 11 13
LITERATURE, NEW
Keywords: Pyrenees -- Fiction; Love stories